O gênero Euastrum ehrenberg ex ralfs sensu lato (conjugatophyceae) do pantanal dos Marimbus do Baiano, Chapada Diamantina, Bahia, Brasil - Costa, Fabiana de Matos (2018)
In aquatic environments, macrophytes contribute as natural substrates that are favorable for the development of desmids. These plants are of great ecological importance and may influence the availability of light, release and assimilation of nutrients to the periphyton. The genus Euastrum is part of the Desmidiaceae family and is characterized mainly by presenting an incision apical U- V shaped. In order to expand the knowledge about Euastrum in the Bahia State, the present study aimed to inventory, describe and illustrate the taxa of the genus associated with the periphyton of three macrophytes (Utricularia foliosa, Cabomba haynesii e Eichhornia azurea), present in the Marimbus of Baiano. The material studied was obtained through bimonthly collections (May/2017 - March/2018). In each sampling period, 10 points were chosen along the floodplain where the three macrophytes co-occurred, totaling 180 sample units. In addition, 60 sample units were collected in the area (April/2011 - February/2012), deposited in the HUEFS collection. Abiotic water variables (temperature, pH, conductivity, total dissolved solids, dissolved oxygen and transparency) were measured during sampling. The collected samples were preserved in Transeau solution and registered in the HUEFS. The material was analyzed in the Phycology‘s Lab (UEFS) and Fiocruz (Bahia) and identified through specialized literature. Thirty - six taxa were identified at infraspecific level, 31 species and 21 varieties other than the typical ones of their respective species. Of these, nine constitute novelties for science (Euastrum abruptum var. chapadae, E. bidentatum var. bahianum, E. diamantinum, E. felisbertii, E. fissum var. nordestinum, E. insulare var. pseudoregnellii, E. marimbusense, E. ornatiscrobiculatum e E. praemorsum var. foersteri), one was registered for the first time in Brazil (Euastrum sublobatum var. sumatranum), and five had the extended geographic distribution to the northeastern Brazil (Euastrum ansatum var. concavum, E. fissum var. angustum, E. groenbladii, E. sibiricum e E. sublobatum var. obtusatum). Of the 36 inventoried taxa, 19 were common the three macrophytes, and the highest taxonomic richness was recorded in the periphyton of U. foliosa (33 taxa), followed by C. haynesii (26) e E. azurea (24). The inventoried taxa were grouped into three groups according to the size and ornamentation of the cells: Group I, composed of 25 taxa, all with a size smaller than 50 μm in length, with three subgroups that differ in relation to ornamentation: A. taxa with central protrusion composed of two or three granules and just above a pair of scrobicles and incision apical V-shaped; B. taxa presenting irregularly arranged granules and scrobicles throughout the semicells face and apical or V-shaped apical incision; C. taxa with little ornate semicell face, usually with a granule or scrobicle and apical incision shallow or smooth; Group II, with four taxa, measuring between 50 - 60 μm in length and presenting cell wall ornamented by many granules and shallow apical incision; and Group III, with seven taxa, with specimens longer than 60 μm in length, characterized by the presence of the semicell face decorated with 1-3 supra-istmal inflations or carrying granules and scrobicules. Most of the taxa were recorded under limnological conditions of slightly basic pH, low conductivity and well oxygenated waters. Regarding the frequency of occurrence, most of the taxa were classified in the rare category (22), followed by the unusual one (6), very frequent (5) and frequent (3). We emphasize the importance of conservation actions of the aquatic macrophytes of the Pantanal of Marimbus do Baiano for the preservation of the periphytic biodiversity. Finally, it is suggested the continuation of studies with polyphasic approach, aiming to broaden the knowledge of the desmids of the Pantanal of the Marimbus and also of other areas of Bahia and Brazil.